A new genus and species of Solenoceridae (Crustacea, Decapoda, Dendrobranchiata) from the Cretaceous (Aptian/Albian) of the Araripe Sedimentary Basin, Brazil - Alencar, Damares Ribeiro; Pinheiro, Allysson Pontes; Saraiva, Antônio Álamo Feitosa; de Oliveira, Gustavo Ribeiro; Santana, William (Zootaxa, 2018)
The first fossil Solenoceridae found from the Cretaceous (Aptian–Albian) is described in the Araripe Sedimentary basin, Priorhyncha feitosai n. gen. n. sp. The material was collected in the strata of the Romualdo Formation, municipality of Trindade, Pernambuco. Characters that permit placement of the new species in Solenoceridae are: a short, dorsally serrated rostrum; a marked cervical groove; and the presence of an antennal spine. Those characters are also diagnostic for Priorhyncha feitosai n. gen. n. sp. when compared to the other Dendrobranchiata shrimp described from this basin.